Peranan Tata Kelola Dalam Penentuan Kas Ditangan - Wirianata, Henny; Viriany; Sari, Vinnetta Ratna; Tanaya, Catherine Carissa (Jurnal Ekonomi, 2023)
This study aims to obtain empirical evidence of the role of governance, namely the structure of the board and audit committee in determining cash holding. The data in the study were taken by purposive random sampling. Data obtained from manufacturing companies listed on the IDX for the 2017-2021 observation period. The data is then processed with E-views. Board size and board meetings have no significant influence. Independent board composition has a significant positive influence. Audit committee members has a significant negative influence. As a control variable, firm size and capital expenditure had no significant effect on cash on holding. Meanwhile, DAR as a control variable has a significant negative influence. Board size, independent board composition, board meetings, and audit committee members, as well as the control variables of firm size, DAR, and capital expenditure have a significant influence on the decision to determine the amount of cash holding.